2016
DOI: 10.1055/s-0036-1584362
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Serous Otitis Media in Children without Otolaryngological Symptoms

Abstract: Introduction Otitis media with effusion is the fluid in the middle ear with no signs or symptoms of acute ear infection. Objective This study aims to research the frequency of serous otitis media in patients referred to the pediatric clinic between 3–16 years of age without any active ear, nose, and throat complaints. Methods This study included 589 children patients (280 boys, 309 girls; mean age: 9.42; range 3–16) who were administered to the pediatric clinic without otolaryngologic complaints. Patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
13
1
1
Order By: Relevance
“…Majority was in the age group of 5-7 years and the mean age was 7.5 years. Similar results were seen in the study conducted by Kocyigit et al 7 Slight male preponderance was noticed in the study. This was in accordance with the observations of Khan et al 8 36% of children presented with features of associated tonsillitis.…”
Section: Discussionsupporting
confidence: 92%
“…Majority was in the age group of 5-7 years and the mean age was 7.5 years. Similar results were seen in the study conducted by Kocyigit et al 7 Slight male preponderance was noticed in the study. This was in accordance with the observations of Khan et al 8 36% of children presented with features of associated tonsillitis.…”
Section: Discussionsupporting
confidence: 92%
“…4 The prevalence of OME has been found to be between 10% to 40% in several studies. 5 6 7 However, in the present study, it was found in 6.9% of the cases. However, none of these patients had any complaints about their ears, which we think is the reason why we found a lower result.…”
Section: Discussioncontrasting
confidence: 77%
“…8 9 In addition, OME not treated for a long period has such risks as language and speech disorders and learning difficulties due to hearing loss in children. 7 9 It is significant that pediatric patients should be evaluated by pediatricians for these reasons. Furthermore, it is essential to receive a reliable medical history from the caretaker, and to inform him/her about the disease and the possible sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Bir diğer etken prematüre doğum ve düşük doğum ağırlığıdır. Hastalığın yaş olarak en sık 6-11 ay arasında saptandığı fark edilmiştir (11,12) . Çalışmamızda otit tanısı alan hastaların 4061'inde (%16.…”
Section: Discussionunclassified